1988
DOI: 10.1097/00000658-198811000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinoma in Young Adults

Abstract: Of 720 patients with gastric carcinoma treated over a 6-year period, 37 (5%) were 35 years of age or younger. They differed from older patients in that the usual sex ratio was altered (18 men: 19 women), and in certain histologic features. Poorly differentiated or undifferentiated lesions predominated (34 patients), and the distribution of histologic types was unusual; two thirds each were of the diffuse type (Lauren classification) or signet ring type (World Health Organization classification), and over three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
79
7
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 13 publications
18
79
7
2
Order By: Relevance
“…Specifically, in patients under 30, the tumour was larger, the undifferentiated type was more frequent, the depth of serosal invasion was greater, the lymphatic involvement was more common, histologically infiltrative growth was prominent and the rate of peritoneal dissemination was higher. (Bloss et al, 1980) and the incidence of gastric cancer in younger patients has been consistent with gastric cancer in several series (Tso et al, 1987;Matley et al, 1988;Okamoto et al, 1988). 2.6% of our patients with gastric cancer were under 30 years of age, findings consistent with the data of Matley and colleagues (1988).…”
Section: Symptomssupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, in patients under 30, the tumour was larger, the undifferentiated type was more frequent, the depth of serosal invasion was greater, the lymphatic involvement was more common, histologically infiltrative growth was prominent and the rate of peritoneal dissemination was higher. (Bloss et al, 1980) and the incidence of gastric cancer in younger patients has been consistent with gastric cancer in several series (Tso et al, 1987;Matley et al, 1988;Okamoto et al, 1988). 2.6% of our patients with gastric cancer were under 30 years of age, findings consistent with the data of Matley and colleagues (1988).…”
Section: Symptomssupporting
confidence: 91%
“…A high frequency of pregnancy in young women with gastric cancer has been noted (Bloss et al, 1980; Matley et al, 1988). As pregnancy most often occurs in this age group, the association could be fortuitous (Matley et al, 1988). The presence of estrogen receptors and intracytoplasmic estradiol in a proportion of patients of all ages fails to explain the preponderance of the female sex among these young cancer patients (Nishi et al, 1987).…”
Section: Symptomsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although in some studies, it proved that age is a significant factor in lifetime (Matley et al, 1988;Mitsudomi et al, 1989;Arveux et al, 1992;Maehara et al, 1995;Haugstvedt et al, 1993;Bucchi et al, 2004;Enzinger and Mayer, 2004;Saidi et al, 2004) there was no significant relationship between age and the lifetime in this study but, in some other studies there was shown that there is not a significant relationship between age and the lifetime (Khedmat et al, 2007;Biglarian et al, 2009;Roshanaei et al, 2010).…”
Section: Discussioncontrasting
confidence: 53%
“…Several clinicopathological factors are involved in determining the prognosis for patients with a gastric cancer (Baba et tion could be fortuitous (Matley et al. 1988).…”
Section: Eiscusimentioning
confidence: 99%